Epidemiology of Sports-Related Eye Injuries Among Athletes in Tianjin, China - Zhang, Jingkai; Zhu, Xinlei; Sun, Zhiyong; Wang, Jiaxing; Sun, Zhuoyu; Li, Jianan; Huang, Yunli; Wang, Tian; Xie, Ruotian; Han, Han; Zhao, Xiao; Song, Yinting; et al. (Frontiers in Medicine, 2021)
Purpose: To investigate the incidence, characteristics, and risk factors of sports-related eye injuries among athletes in Tianjin, China. Methods: Cross-sectional study carried out from 03/2018 to 10/2018. Athletes were from Tianjin University of Sports, Tianjin Vocational College of Sports, and Tianjin provincial sports teams for general investigation. In total, 1673 athletes were invited and 1413 participated in the study (response rate of 84.5%). Results: In total, 1413 athletes were enrolled; 151 had suffered from sports-related eye injuries, for a incidence of 10.7% (95% confidence interval [CI]: 9.1%-12.0%). Handball (38.5%) was the sport with highest incidence of eye injuries, followed by water polo(36.4%) and diving(26.7%). Overall, 42.4% of athletes were injured by ball, and 22.5% of injuries came from teammates. Eye injuries usually occurred during training(64.2%) and competitions(14.6%). Adnexa wound(51.7%) was the most common type of injuries. About 11.9% of athletes with eye injuries had impaired vision; 66.7% failed to see doctors in time. Athletes <18 years of age had higher risk of eye injuries (odds ratio [OR]=1.60, 95%CI: 1.06-2.40). Athletes with lower family income (<1000 RMB) were risk population for sports-related eye injuries (OR=3.91, 95%CI: 2.24-6.82). Training >4 h a day increased the risk of eye injuries (OR: 2.21, 95%CI: 1.42-3.43). Conclusions: The incidence of sports-related eye injuries among athletes was 10.7% in Tianjin, China. Handball, water polo, and diving were the most common activities of injury. Age, family income, and training time were risk factors for sports-related eye injuries.